1987
DOI: 10.1111/j.1399-3054.1987.tb04277.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of chilling on the activity of C4 enzymes in two ecotypes of Echinochloa crus‐galli from sites of contrasting climates

Abstract: Five‐week‐old plants of Echinochloa crusgalli (L.) Beauv. from Mississippi and from Québec grown under controlled conditions were subjected to dark chilling for 10 h at 5°C or light chilling treatments for 14 h at 7°C under hight light (1 000 μmol m−2 s−1). The activities of four C4 enzymes of Québec plants, measured 4 h after the completion of the cold treatment, were not affected by the chilling treatment in the dark. The activities of pyruvate, Pi dikinase (PPDK; EC 2.7.9.1) and NADP+‐malic enzyme (NADP+‐ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Changes in the activity of this enzyme would be consistent with the observed decrease in photosynthesis as a function ofintercellular CO 2 partial pressures in the Triangle T population grown in the cool chamber. Ecotypic differentiation in populations of Echinochloa crus-galli from Quebec and Mississippi has been linked to differences in the activity ofpyruvate, Pi dikinase following exposure to low temperatures (0 and 10 C) (Simon, 1987). Variation in the cold temperature inactivation of this enzyme has also been noted in cultivars of Zea mays, with cool temperature strains maintaining the lowest inactivation after being subjected to 0 C ( Shirahashi et al, 1978).…”
Section: Methodsmentioning
confidence: 99%
“…Changes in the activity of this enzyme would be consistent with the observed decrease in photosynthesis as a function ofintercellular CO 2 partial pressures in the Triangle T population grown in the cool chamber. Ecotypic differentiation in populations of Echinochloa crus-galli from Quebec and Mississippi has been linked to differences in the activity ofpyruvate, Pi dikinase following exposure to low temperatures (0 and 10 C) (Simon, 1987). Variation in the cold temperature inactivation of this enzyme has also been noted in cultivars of Zea mays, with cool temperature strains maintaining the lowest inactivation after being subjected to 0 C ( Shirahashi et al, 1978).…”
Section: Methodsmentioning
confidence: 99%
“…The depression of photosynthesis for short or long periods of time and even its irreversible inhibition is a prominent and common symptom of chilling injury in all sensitive plants (see the reviews by Berry and Björkman 1980, Long et al 1994, Allen and Ort 2001). In C 4 plants, it has been associated with direct alterations on the kinetics of CO 2 assimilation via the C 4 pathway and the irreversible damage to the chloroplast structure and development (Slack et al 1974, Simon 1987, Nie et al 1995, Haldimann 1996, Kingston‐Smith et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…(bamyard grass; Poaceae) from Quebec (QUE) and Mississippi (MISS) have demonstrated clear ecotypie differentiation between these populations with regard to their response to cold-temperature treatments or to climate (Fotvin and Simon 1990, Simon andHatch 1994). Comparative studies ranging from the analysis of suri'ival, allocation of growth and reproductive capacity (Potvin 1986(Potvin , 1991, to their response to photosynthesis (Potvin et al 1986, Polvin 1987, carbon translocation (Potvin et al 1985) and thermal and kinetic studies of key C^ enzymes (Simon et al 1984, Potvin et al 1986, Simon 1987. Lapointe et al 1989, Simon and Vairinhos 1991, Simon and Hatch 1994 have shown that, compared to MISS plants, QUE plants were consistently more tolerant to cold temperatures (review in Potvin and Simon 1990).…”
mentioning
confidence: 99%